Algebra conundrum

Algebra Level 3

a 2 4 3 7 = 0 , a 6 1 a 3 = ? a^2 - 4\sqrt3 - 7 = 0 \qquad , \qquad \frac{a^6 - 1}{a^3} = \ ?

a > 0 a > 0 .

30√3 40√3 40 30

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

We have that a 2 = 4 3 + 7. a^{2} = 4\sqrt{3} + 7. To find a , a, we start by forming the equation

4 3 + 7 = m + n 3 , \sqrt{4\sqrt{3} + 7} = m + n\sqrt{3},

where m , n m,n are integers. Squaring both sides yields

4 3 + 7 = m 2 + 3 n 2 + 2 m n 3 . 4\sqrt{3} + 7 = m^{2} + 3n^{2} + 2mn\sqrt{3}.

Equating respective rational and irrational components yields that

m n = 2 , m 2 + 3 n 2 = 7 m 2 + 12 m 2 7 = 0 mn = 2, m^{2} + 3n^{2} = 7 \Longrightarrow m^{2} + \dfrac{12}{m^{2}} - 7 = 0

m 4 7 m 2 + 12 = 0 ( m 2 3 ) ( m 2 4 ) = 0. \Longrightarrow m^{4} - 7m^{2} + 12 = 0 \Longrightarrow (m^{2} - 3)(m^{2} - 4) = 0.

Now since we require that m , n m,n be integers and a > 0 , a \gt 0, we see that m = 2 , n = 1. m = 2, n = 1. (We could have done this by simple observation, but it's informative to outline the general process.)

Thus a = 2 + 3 a = 2 + \sqrt{3} and a 2 = 7 + 4 3 a^{2} = 7 + 4\sqrt{3}

a 3 = ( 2 + 3 ) ( 7 + 4 3 ) = 26 + 15 3 . \Longrightarrow a^{3} = (2 + \sqrt{3})(7 + 4\sqrt{3}) = 26 + 15\sqrt{3}.

Now since ( 26 + 15 3 ) ( 26 15 3 ) = 1 (26 + 15\sqrt{3})(26 - 15\sqrt{3}) = 1 we have that

a 6 1 a 3 = ( 26 + 15 3 ) 2 1 26 + 15 3 × 26 15 3 26 15 3 = \dfrac{a^{6} - 1}{a^{3}} = \dfrac{(26 + 15\sqrt{3})^{2} - 1}{26 + 15\sqrt{3}} \times \dfrac{26 - 15\sqrt{3}}{26 - 15\sqrt{3}} =

( ( 26 + 15 3 ) 2 1 ) ( 26 15 3 ) = ( 26 + 15 3 ) ( 26 15 3 ) = 30 3 . ((26 + 15\sqrt{3})^{2} - 1)(26 - 15\sqrt{3}) = (26 + 15\sqrt{3}) - (26 - 15\sqrt{3}) = \boxed{30\sqrt{3}}.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...